2009
DOI: 10.1016/s0079-6123(09)17723-3
|View full text |Cite
|
Sign up to set email alerts
|

Life can be worth living in locked-in syndrome

Abstract: The locked-in syndrome (LIS) describes patients who are awake and conscious but severely deefferented leaving the patient in a state of almost complete immobility and loss of verbal communication. The etiology ranges from acute (e.g., brainstem stroke, which is the most frequent cause of LIS) to chronic causes (e.g., amyotrophic lateral sclerosis; ALS). In this article we review and present new data on the psychosocial adjustment to LIS. We refer to quality of life (QoL) and the degree of depressive symptoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
106
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(122 citation statements)
references
References 63 publications
9
106
1
6
Order By: Relevance
“…From an exterior point of view, it seems difficult to endure such a handicap without failing in experiencing a continuous self. When asked if they themselves would accept to be kept alive in such a situation, medical teams often answer that they would not, predicting a negative experience for the patients Lule et al, 2009). Most of the patients, on the contrary, report a positive wellbeing Bruno et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…From an exterior point of view, it seems difficult to endure such a handicap without failing in experiencing a continuous self. When asked if they themselves would accept to be kept alive in such a situation, medical teams often answer that they would not, predicting a negative experience for the patients Lule et al, 2009). Most of the patients, on the contrary, report a positive wellbeing Bruno et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…LIS patients show quadriplegia, mutism, and bilateral facial palsy with preservation of vertical gaze and upper eyelid movements; consciousness and cognitive abilities are spared (Schnakers et al, 2008). LIS patients are able to interact with the environment solely through eye-coded communication; despite this extreme degree of motor disability, LIS patients appear emotionally adapted to their severe physical conditions (Cappa et al, 1985;Lulé et al, 2009). The causal ventral pontine lesion in LIS patients usually spares neural structures involved in producing spontaneous facial expressions (Hopf et al, 1992;Töpper et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Bruno and colleagues surveyed a group of 65 patients with locked-in syndrome, 72% of whom indicated that they were happy, with a greater period in the locked-in state positively correlated with patient happiness (Bruno et al 2011). Other studies have found that patient-evaluated quality of life was not significantly different from healthy controls (with the exception being on scales of physical function) (Lule et al 2009;Rousseau et al 2013). The fact that these patients report that they are happy in their state suggests that it may not be in their best interests to withdraw them from life sustaining treatment.…”
Section: Desires No Longer Endorsedmentioning
confidence: 99%